2015
DOI: 10.1093/hmg/ddv503
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial disease genesCOA6,COX6BandSCO2have overlapping roles in COX2 biogenesis

Abstract: Biogenesis of cytochrome c oxidase (CcO), the terminal enzyme of the mitochondrial respiratory chain, is a complex process facilitated by several assembly factors. Pathogenic mutations were recently reported in one such assembly factor, COA6, and our previous work linked Coa6 function to mitochondrial copper metabolism and expression of Cox2, a copper-containing subunit of CcO. However, the precise role of Coa6 in Cox2 biogenesis remained unknown. Here we show that yeast Coa6 is an orthologue of human COA6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 45 publications
5
60
0
Order By: Relevance
“…55 In retrospect, these findings are not that surprising given the relative severity of the copper deficiency in various SCO1 cell types, 45 and the fact that SCO1 catalyzes the transfer of copper to the Cu A site of COX2 in a reaction that is facilitated by SCO2 and COA6. 54, 56, 58, 87 These observations in fact collectively support the idea that SCO1 sits at the head of a mitochondrial pathway, and that its functional status directly impinges upon COX assembly and the generation of a signal that regulates copper homeostasis (Figure 2). 23, 24 The exact identity of this mitochondrial signal and how it is transduced to copper handling machinery localized elsewhere in the cell is not yet known.…”
Section: Mitochondrial Copper Chaperones Play a Key Role In The Regulsupporting
confidence: 65%
See 1 more Smart Citation
“…55 In retrospect, these findings are not that surprising given the relative severity of the copper deficiency in various SCO1 cell types, 45 and the fact that SCO1 catalyzes the transfer of copper to the Cu A site of COX2 in a reaction that is facilitated by SCO2 and COA6. 54, 56, 58, 87 These observations in fact collectively support the idea that SCO1 sits at the head of a mitochondrial pathway, and that its functional status directly impinges upon COX assembly and the generation of a signal that regulates copper homeostasis (Figure 2). 23, 24 The exact identity of this mitochondrial signal and how it is transduced to copper handling machinery localized elsewhere in the cell is not yet known.…”
Section: Mitochondrial Copper Chaperones Play a Key Role In The Regulsupporting
confidence: 65%
“…28 Its copper is coordinated via a Cx 3 C motif and a conserved histidine residue, 5153 and is transferred directly to the Cu A site of COX2 54 in a reaction that also requires the COX assembly factors SCO2 and COA6 (Figure 1). 5558 Interestingly, a multitude of other IMS-localized proteins containing canonical twin Cx 9 C motifs have been implicated in COX assembly in yeast, 59 many of which have evolutionarily conserved mammalian homologues with undefined functions. We fully expect that future studies will identify members of this protein family that fulfill unique roles in delivering copper to COX, prioritizing copper utilization within the IMS, and regulating the generation and transduction of a copper-dependent, mitochondrial signal.…”
Section: Copper In Mitochondriamentioning
confidence: 99%
“…The presence of Cox20p in B4 and of Cox18p in both B3 and B4 suggests that the interaction of Cox18p with the Cox2p precursor precedes that of Cox20p. Yeast Sco1p and Coa6p, like their human counterparts, form complexes with Cox2p intermediates (39,40). In both cases the interactions appear to be transient as only a small fraction of the newly translated Cox2p co-immunopurified with tagged Sco1p and Coa6p.…”
Section: Cox2p Assembly Module Of Yeast Cytochrome Oxidasementioning
confidence: 99%
“…Work by Morgada et al . showed that Sco2 functions as a reductase for both, Sco1 and Cox2 (CoxB‐like), in a process that is possibly assisted by yet another assembly factor, COA6 . Finally, investigating Cu A synthesis in vitro with a bacterial sytem, Abriata et al .…”
Section: The Role Of Tlpa In Attuning Apo‐scoi and Apo‐coxb For Metalmentioning
confidence: 99%
“…More specifically, the intermembrane space protein Cox17 was described not only as a metallochaperone transferring Cu 1+ to Sco1 (ScoI-like) [47], but also as a possible reductase for the copperbinding site of Sco1 [48]. Work by Morgada et al [39] showed that Sco2 functions as a reductase for both, Sco1 and Cox2 (CoxB-like), in a process that is possibly assisted by yet another assembly factor, COA6 [49]. Finally, investigating Cu A synthesis in vitro with a bacterial sytem, Abriata et al [34] reported that a ScoI-like protein was fully sufficient to reduce the oxidized Cu A -binding site in ba 3 -type Cox subunit II of T. thermophilus.…”
Section: Pcucmentioning
confidence: 99%